Lourdes: storie di miracoli Genesi e sviluppo di una devozione planetaria - Di Marco, Alessandro (Premio Istituto Sangalli per la storia religiosa, 2016)
The aim of this work is to identify the factors which contributed to create Lourdes' success. This analysis starts from the comparison between the 18 apparitions in Lourdes with some similar and contemporary episodes occurring in France, but with a somewhat different outcome, intended as success among the pilgrims. The initial historical, political and cultural contextualization work is accompanied by the analysis of some key aspects of the Catholic Church of that time. In reference to the purpose of the text, two areas are analysed more in-depth: medical science and literature, both closely connected with the question of miracles.